2005
DOI: 10.1111/j.1365-2125.2005.02430.x
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide in the treatment of rheumatoid arthritis. An analysis of predictors for treatment continuation

Abstract: AimsTo determine factors predictive for leflunomide drug survival in an outpatient population with rheumatoid arthritis in a setting of care-as-usual. MethodsA standard dataset was collected from medical records of consecutive outpatients on leflunomide treatment for rheumatoid arthritis between January 2000 and June 2003. The dataset consisted of patient, disease and treatment characteristics at the star t of leflunomide treatment, and data on leflunomide use. ResultsLeflunomide was started in 279 patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…found that ESR did not influence response to HCQ monotherapy [34] but in another study a low baseline CRP was the only predictor of a favorable response to HCQ monotherapy in early RA patients (OR (CRP ≤10 mg/L) = 3.6, 95% CI 2.2 to 6.0) [35]. van Roon and colleagues identified ESR <35 mm.h -1 at treatment start to predict higher leflunomide survival (hazard ratio (HR) = 1.38, 95% CI 1.01 to 1.88) [36] and likewise, high ESR at disease onset and at DMARD initiation predicted early discontinuation of treatment in an established RA study (HR = 1.05 per 10 mm.h -1 increase, 95% CI 1.02 to 1.08) [53]. Contrary to these findings, Capell et al .…”
Section: Clinical Predictors Of Responsementioning
confidence: 99%
See 2 more Smart Citations
“…found that ESR did not influence response to HCQ monotherapy [34] but in another study a low baseline CRP was the only predictor of a favorable response to HCQ monotherapy in early RA patients (OR (CRP ≤10 mg/L) = 3.6, 95% CI 2.2 to 6.0) [35]. van Roon and colleagues identified ESR <35 mm.h -1 at treatment start to predict higher leflunomide survival (hazard ratio (HR) = 1.38, 95% CI 1.01 to 1.88) [36] and likewise, high ESR at disease onset and at DMARD initiation predicted early discontinuation of treatment in an established RA study (HR = 1.05 per 10 mm.h -1 increase, 95% CI 1.02 to 1.08) [53]. Contrary to these findings, Capell et al .…”
Section: Clinical Predictors Of Responsementioning
confidence: 99%
“…RF is associated with persistent disease and radiographic progression [21,81-83] but its role in predicting response to treatment is less clear. A large number of studies, comprising a considerable number of patients, showed that RF status does not predict response to MTX and other DMARDs in both early and established RA [1,14,23,25,27-29,34,36,37,42,45,53,55,66,84]. However, in the study by Wessels et al [22] RF-positivity alone presented a trend towards worse response to MTX monotherapy in early RA patients; RF-positive smokers were definitely worse responders.…”
Section: Nongenetic Biomarkers Of Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Because of the very long half-life of the metabolite (about 2 weeks), a loading dose of 100 mg/day for 3 days (in adult-sized patients) is used to facilitate rapid attainment of steady-state levels. The onset of effect may begin as early as 4 weeks after drug initiation, and improvement continues through about 5 months of treatment [ 39 ].…”
Section: Other Agentsmentioning
confidence: 99%
“…Using multivariate analysis, a strong effect was seen for “attending rheumatologist”, suggesting that physician behavior in response to side effects is an important determinant. 135 …”
Section: Use Of Leflunomide In Clinical Practicementioning
confidence: 99%